Pengaruh Religiusitas dan Pendidikan Karakter Siswa (Disiplin, Jujur, Sopan Santun dan Bertanggung Jawab) Terhadap Agresivitas di MI Istiqlal Jakarta - Al-Nur, Widya Rahmawati; Viranda, Chintia; Handayani, Wiwik; Irawan, Fajar (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Religiosity is the ability of individuals to understand, live, and apply the values of their religion in everyday life. Character education is the cultivation of ways of thinking and behaving that are characteristic of each individual to live and work together, both within the family and in society. Meanwhile, aggression is an emotional outburst as a reaction to individual failure which is shown in the form of damaging people or objects with an intentional element expressed in words (verbal) and non-verbal behavior. In the research that will be conducted, the researcher will test whether there is an influence of students' religiosity and character education on the level of aggressiveness at MI Istiqlal Jakarta. The method used is quantitative with multiple linear regression analysis, the subject is 165 students of which 69 are male and 96 are female. The sampling technique used is quota sampling by collecting data using a Likert scale with 4 answer choices. The results in the study found that the R square was 0.185, which means 18.5% of the influence of religiosity and character education on aggressiveness. While 81.5% is influenced by other variables